Users’ Satisfaction with Internet Service Performance-Based on User Log - Ojebode, Member; Akhigbe, Bernard Ijesunor (IPTEK The Journal for Technology and Science, 2025)
We are currently on the cusp of a digital era when people engage Internet services (Int-Sevs) ceaselessly for sundry purposes such as learning, teaching, and research. However, the lack of sufficient understanding of user satisfaction still poses a huge challenge to Int-Sevs adaption to users’ dynamic needs and the provision of required services in real-time within the university’s context. This understanding is needful concerning what influences the performance of the Int-Sevs of a university. This paper, therefore, analyses the user log of about 65000 log items generated by 120 users of a university’s internet services that were collected over three months. The mixed-method approach was adopted. Thus, the two-step clustering and crosstabulation techniques were applied to identify natural groupings and examine them for existing relationships (respectively) to determine the existence of user satisfaction. The results showed a significant association and relationship between user satisfaction and Key Performance Indicators (KPIs). The study concluded that with data and efficient techniques, KPIs with user-centric criteria like user satisfaction could be investigated to find what influences the performance of a university’s IntSevs. The quality of users’ experience was omitted and left to be considered in the future in a conceivably longitudinal study.